STEREOTIP ANTAR ETNIS DALAM DISINTEGRASI SOSIAL DI KOTA KENDARI - La Iba (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
This research is motivated by ethnic diversity in the city of Kendari which often led to the social friction and mostly constructed as social disintegration which stems from a personal feud then escorted to the ethnic problem. This feeling needs to be tested in a scientific sphere in which an issue can not be accepted and taken for granted without conducting the assessment, so that later statements and conclusions drawn have a proper scientific basis. According to the writer’s presumption, social disintegration that has occurred is not understood as a matter of social common, but can be traced roots of the problem, especially coupled with the intensity of the frequent occurrence. So it can be assumed that the conflict happened because wake of the negative stereotypes of each ethnicity, so that social integration is often cracked though only bothered with trivial reasons. The desired result of this research was to determine the ethnic stereotypes of the local in the city of Kendari which includes ethnic Tolaki, ethnic Muna and Buton ethnic integration always torn along with the passing of time. This study used a qualitative approach, the subject was the students and the community in the Kambu Village and Lalolara Village. Data was collected through observation, interviews, and questionnaires. The data were analyzed qualitatively. Keywords: stereotypes, ethnic, disintegration, social